Cross‐sectional analysis of the dermoscopic patterns and structures of melanocytic naevi on the back and legs of adolescents. (1st December 2015) - Fonseca, M.; Marchetti, M.A.; Chung, E.; Dusza, S.W.; Burnett, M.E.; Marghoob, A.A.; Geller, A.C.; Bishop, M.; Scope, A.; Halpern, A.C.
Summary: Background: Junctional (flat) naevi predominate on the extremities, whereas dermal (raised) naevi are found primarily on the head, neck and trunk. Few studies have investigated the anatomical site prevalence of melanocytic naevi categorized using dermoscopy. Objectives: To identify the prevalence of dermoscopic patterns and structures of naevi from the back and legs of adolescents. Methods: Dermoscopic images of acquired melanocytic naevi were obtained from the back and legs of students from a population‐based cohort in Framingham, Massachusetts. Naevi were classified into reticular, globular, homogeneous or complex dermoscopic patterns. Multinomial logistic regression modelling assessed the associations between dermoscopic pattern and anatomical location. Results: In total 509 participants (mean age 14 years) contributed 2320 back naevi and 637 leg naevi. Compared with homogeneous naevi, globular and complex naevi were more commonly observed on the back than the legs [odds ratio (OR) 29·39, 95% confidence interval (CI) 9·53–90·65, P < 0·001 and OR 6·8, 95% CI 2·7–17·14, P < 0·001, respectively], whereas reticular lesions were less likely to be observed on the back than on the legs (OR 0·67, 95% CI 0·54–0·84, P = 0·001). Naevi containing any globules were more prevalent on the back than on the legs (25% vs. 3·6%, P < 0·001). Naevi containing any network were more prevalent on the legs than on the back (56% vs. 40·6%, P < 0·001). Conclusions: These findings add to a robust body of literature suggesting that dermoscopically defined globular and reticular naevi represent biologically distinct naevus subsets that differ in histopathological growth pattern, age‐ and anatomical‐site‐related prevalence, molecular phenotype and aetiological pathways.